2023
DOI: 10.3390/ijms241612767
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-146a—A Key Player in Immunity and Diseases

Irina Gilyazova,
Dilara Asadullina,
Evelina Kagirova
et al.

Abstract: miRNA-146a, a single-stranded, non-coding RNA molecule, has emerged as a valuable diagnostic and prognostic biomarker for numerous pathological conditions. Its primary function lies in regulating inflammatory processes, haemopoiesis, allergic responses, and other key aspects of the innate immune system. Several studies have indicated that polymorphisms in miRNA-146a can influence the pathogenesis of various human diseases, including autoimmune disorders and cancer. One of the key mechanisms by which miRNA-146a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 183 publications
0
4
0
Order By: Relevance
“…This upregulation of miR-146a played a role in promoting viral replication by inhibiting the production of interferon type I [33]. Moreover, it has been observed level of miR-146a can mitigate lung cell damage by suppressing inflammatory responses [34]. Regarding miR-21, a study by Nersisyan et al [35] demonstrated an eight-fold upregulation of miR-21-3p during lung infection caused by SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 98%
“…This upregulation of miR-146a played a role in promoting viral replication by inhibiting the production of interferon type I [33]. Moreover, it has been observed level of miR-146a can mitigate lung cell damage by suppressing inflammatory responses [34]. Regarding miR-21, a study by Nersisyan et al [35] demonstrated an eight-fold upregulation of miR-21-3p during lung infection caused by SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 98%
“…It has an important role in the regulation of immune system cell differentiation, inflammatory cytokines, and various immune conditions. 8,9 MiR-146a is considered a negative regulator of the immune response through the regulation of two genes, tumor necrosis factor (TNF) receptor-related factor-6 and interleukin-1 (IL-1) receptor-related kinase-1. 10,11 The same genes are considered to cause abnormal activation of the nuclear factor (NF)-kB signaling pathway that regulates the expression of some of the inflammatory mediators such as IL-6, IL-1β, TNF-α and some metalloproteinases (matrix metalloproteinase-13 and a disintegrin and metalloproteinase with thrombospondin motifs-5).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA‐146a (miR‐146a) is a member of the miRNA family and is encoded on chromosome 5q33.3. It has an important role in the regulation of immune system cell differentiation, inflammatory cytokines, and various immune conditions 8,9 . MiR‐146a is considered a negative regulator of the immune response through the regulation of two genes, tumor necrosis factor (TNF) receptor‐related factor‐6 and interleukin‐1 (IL‐1) receptor‐related kinase‐1 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…In the physiological state, miR-146a-5p expression is restricted to immune cells and negatively inhibits the innate and adaptive immune response by regulating certain adapters or transcription factors, including, e.g., the signal transducer and activator of transcription 1 (STAT1) [39]. Moreover, miR-146a-5p influences gene expression through multiple signaling pathways such as TNF, NF-κB, and MEK-1/2, and JNK-1/2 [40]. The expression levels of miR-146a-5p were increased in patients with kidney diseases, with focal segmental glomerulosclerosis, and membranoproliferative glomerulonephritis [41].…”
Section: Introductionmentioning
confidence: 99%